TECHNICAL AND ECONOMIC UNIFICATION ASPECTS MTZ «BELARUS» TRACTOR TRANSMISSION - I. V. Emelianovich (Наука и техника)
The paper reveals role and peculiar features of design elements of complicated machinery that ensures higher compatibility of national products under crisis conditions. Peculiar features and economic effect due to in-time modernization are analyzed from the side of a manufacturer and a consumer as well.